Peculiarities of channeling and generated radiation of relativistic electrons in the main charged axes of lithium hydride crystal - Maksyuta, N.V.; Vysotskii, V.I.; Efimenko, S.V.; Slinchenko, Yu.A. (Вопросы атомной науки и техники, 2021)
The paper deals with the calculation of electron interaction potentials with the main charged [110] axes in a lithium hydride crystal at T = 300, 600, and 900 K temperatures. For relativistic electrons with Lorentz factors γ = 50, 75, 100 the energy and corresponding wave functions of transverse levels of channeling motion are found numerically. The radiation spectra of channeling electrons with (and without) accounting an angular dispersion are calculated on the basis of these data.